2023
DOI: 10.3390/ph16060839
|View full text |Cite
|
Sign up to set email alerts
|

Synergy of Plant Essential Oils in Antibiotic Therapy to Combat Klebsiella pneumoniae Infections

Mariana Romo-Castillo,
Victor Andrés Flores-Bautista,
Silvia Laura Guzmán-Gutiérrez
et al.

Abstract: Increased antibiotic resistance presents a health problem worldwide. The World Health Organization published a list of pathogens considered a priority for designing new treatments. Klebsiella pneumoniae (Kp) is a top-priority microorganism, highlighting the strains that produce carbapenemases. Developing new efficient therapies or complementing existing treatments is a priority, and essential oils (EOs) provide an alternative. EOs could act as antibiotic adjuvants and enhance antibiotic activity. Employing sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Therefore, these results represent further confirmation of the series of data in the literature which have highlighted the ability of EOs to enhance the effects of antibiotics in oil-, antibiotic-, and strain-specific manner. Similarly to those we analyzed, EOs containing carvacrol, eucalyptol, eugenol, and thymol have been demonstrated to exercise a synergistic effect in combination with antibiotics [17,18,28,41]. Findings observed in P. aeruginosa appear relevant if we consider that it is widely recognized as a prototype of a "multidrug-resistant pathogen" that is frequently associated with increased morbidity and mortality.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Therefore, these results represent further confirmation of the series of data in the literature which have highlighted the ability of EOs to enhance the effects of antibiotics in oil-, antibiotic-, and strain-specific manner. Similarly to those we analyzed, EOs containing carvacrol, eucalyptol, eugenol, and thymol have been demonstrated to exercise a synergistic effect in combination with antibiotics [17,18,28,41]. Findings observed in P. aeruginosa appear relevant if we consider that it is widely recognized as a prototype of a "multidrug-resistant pathogen" that is frequently associated with increased morbidity and mortality.…”
Section: Discussionmentioning
confidence: 72%
“…In recent years, various approaches have been developed, including the combination of antibiotics with EOs, to investigate the synergic effect of them, which could be more effective in counteracting bacterial resistance [13][14][15][16][17]. Romo-Castillo et al demonstrated the potential of EOs extracted from Rosmarinus officinalis, Thymus vulgaris, Mentha piperita, and Curcuma longa to combat K. pneumoniae by applying a synergic therapy for antibiotics [18]. The effects of Protium heptaphyllum EO (PHEO) alone and in combination with antibiotics against polymyxin-resistant K. pneumoniae isolates were also analyzed [19].…”
Section: Introductionmentioning
confidence: 99%
“…Our group found that Thymus vulgaris, Mentha piperita, Rosmarinus officinalis, and Curcuma longa essential oils effectively against Kpn clinical strains, affecting the hypermucoviscosity phenotype. These findings indicate that essential oils are the best choice to combat mucus production and biofilm-forming strains [121]. However, more studies on essential oils are needed to investigate their safety profile, characterise their mechanism of action, optimise their dose, and observe possible adverse effects in human cells.…”
Section: The Potential Of Plant-origin Components As a New Treatment ...mentioning
confidence: 99%
“…Our research group is focused on developing plant compounds that can be employed as synergic therapy with antibiotics (Figure 7). Our last report analysed the potential of essential oils (EOs) against Klebsiella pneumoniae infections [121]. We selected EOs with a zone diameter similar to antibiotics' standard breakpoints (>15 mm) and a synergic effect with antibiotics.…”
Section: Perspectivesmentioning
confidence: 99%